Oral sucrose for analgesia in children aged between 3 months and 3 years undergoing transurethral bladder catheterisation: A randomised, double‐blinded, clinical trial. (17th July 2019) - London, Kevin; Watson, Hamish; Kwok, Samson; Nanan, Ralph; Liu, Anthony
Abstract : Aim: Many children admitted to hospital undergo invasive, painful and stressful procedures, including children who are not toilet trained undergoing transurethral bladder catheterisation (TUBC). Oral sucrose is commonly given to children to reduce procedural pain. In this study, we evaluated the effectiveness of oral sucrose in reducing procedural pain in children aged between 3 months and 3 years undergoing TUBC. Methods: This study was a randomised, double‐blind, placebo‐controlled study conducted at Nepean Hospital, Sydney, Australia from June 2005 to June 2010. A total of 40 participants requiring TUBC for diagnostic evaluation were included. The participants were randomly assigned to receive 4 mL of 75% oral sucrose ( n = 20) or a placebo (sterilised water) ( n = 20). The primary outcomes were changes in two paediatric pain scale scores (the FLACC pain scale and the OUCHER pain scale), assessed by the parent/guardian(s), the doctor performing the TUBC and the nurse assisting. The secondary outcomes were physiological (changes in heart rate) and behavioural pain (crying) indicators. Results: Of the outcome measures, 65% favoured the oral sucrose group, 31% favoured the placebo group, and 4% found no difference between the oral sucrose and placebo groups. Conclusion: While the trends favouring the sucrose group in this study were encouraging, as the results were not statistically significant, there was insufficient evidence to demonstrate the effectiveness of oral sucrose in reducing procedural pain in children aged between 3 months and 3 years undergoing TUBC.